2001
DOI: 10.1097/00005537-200102000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Voice After Laryngectomy Using a Sound‐Producing Voice Prosthesis

Abstract: The mechanism is feasible and does not result in unacceptable airflow resistance. For this new mechanism of alaryngeal voice to become an established technique for postlaryngectomy voice restoration, a voice suitably pitched for male laryngectomees has to be generated and a large part of the melodic and dynamic range of the sound source has to be attainable within physiological airflow rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…De Vries et al 4,5 developed a different kind of VPE, consisting of an outwards-striking silicone rubber lip placed in a square housing. In clinical tests, however, Van der Torn et al 29 observed that the functioning of the silicone rubber lip was also sensitive to the mucus that entered the prototype. The lip sometimes stuck to the interior of its housing.…”
Section: Introductionmentioning
confidence: 99%
“…De Vries et al 4,5 developed a different kind of VPE, consisting of an outwards-striking silicone rubber lip placed in a square housing. In clinical tests, however, Van der Torn et al 29 observed that the functioning of the silicone rubber lip was also sensitive to the mucus that entered the prototype. The lip sometimes stuck to the interior of its housing.…”
Section: Introductionmentioning
confidence: 99%
“…4 An example of frequency spectrum of sound produced by voice producing element at driving pressure of 2 kPa. F 0 corresponds to the vibration frequency of the oscillator.…”
Section: Equipment and Analysis Methodsmentioning
confidence: 99%
“…4, 2013 Journal of Advanced Mechanical Design, Systems, and Manufacturing the proposed methods. However, both produce only monotonous voices, and it is reported that their functions deteriorate as secretions adhere to the surface of the material (4) . Tack et al succeeded in changing the pitch of the voice by an average of 5.1 semitones according to the expiratory pressure at a stable and appropriate pitch by placing two elastic resin membranes parallel inside the shunt valve such that they act as a vibrating valve (5), (6) .…”
mentioning
confidence: 99%
“…Designs have been recently developed and tested (De Vries et al, 2000;Van der Torn et al, 2001;Tack et al, 2006). These designs incorporate a vibrating reed-or membrane-type element within the shunt valve lumen, the structural characteristics of which yield flow-induced vibrations at reasonable lung pressures.…”
Section: Introductionmentioning
confidence: 99%